Challenging case of severe acute asthma in a mechanically ventilated patient managed with sevoflurane - Satheesh Munusamy (21606281) (2023)
Acute severe bronchial asthma is a chronic inflammatory disease characterized by hyperresponsiveness of the airways leading to bronchoconstriction. We present a case of refractory life‐threatening bronchial asthma that was managed with sevoflurane gas along with the standard treatment and achieved stability and clinical improvement through its bronchodilator and anesthetic effect. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.6571